RACISM: A PUBLIC HEALTH PROBLEM IN SANTANDER, COLOMBIA - Ocampo Ramirez, Vivien Hidela (Instituto de Investigaciones Socioeconómicas, 2021)
“Public Health has evolved, which has allowed integrating problems from a holistic view and with a differential approach articulated with the social sciences for the well-being of all people locally, nationally and globally level” (Vergara Quintero 2007,p.43). It is appropriate to mention that based on a qualitative research in public health, carried out in 2019 to the afro descendant people of the municipality of Girón, Santander, Colombia where “the design of the life stories” (Berteaux, De, and Bellaterra 2006, p.225) was implemented, from an ethnosociological and interpretive perspective; the findings found evidence that racism is considered a public health problem. Indeed, this study documented in their narratives the perception “Living well"(Sánchez et al ,2006, p.31), which is summarized in well-being during the course of their lives, and on which it depends directly on the categories embedded within the theoretical framework of intersectionality in Public Health(Bauer 2014,p.11), Intersectionality (Bastos, Harnois, and Paradies 2018, p.2), Intersectionality in the course of life (Ferrer et al. 2017,p.3) and Spirituality (Arocha 2012, p.5). The limitation of this study was due to logistical situations in the transcripts of the life stories.